2012
DOI: 10.1016/j.annepidem.2011.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Parental Age and Autism Spectrum Disorders

Abstract: PURPOSE-We sought to study the possible association between parental age and autism spectrum disorder (ASD) by using both a cohort design and a sibling design. RESULTS-A total of 9556 children were diagnosed with an ASD. Both maternal and paternal age were associated with a greater risk of ASD in the offspring (hazard ratios ranging from 1.21 (1.10-1.34) to 1.65 (1.09-2.48) depending on combinations of parental age categories; <35, 35-39, and 40+ years). For mothers younger than 35 years, the risk of ASD incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
104
3
12

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(132 citation statements)
references
References 24 publications
13
104
3
12
Order By: Relevance
“…106 Some studies have found paternal and maternal ages to be independent risk factors for ASD after adjusting for spousal age, [126][127][128] and no evidence for a synergistic effect. 117 Other studies have accounted for multicollinearity of maternal and paternal ages and found that advanced maternal age was the primary independent contributor of the parental age effect.…”
Section: Twomentioning
confidence: 99%
See 2 more Smart Citations
“…106 Some studies have found paternal and maternal ages to be independent risk factors for ASD after adjusting for spousal age, [126][127][128] and no evidence for a synergistic effect. 117 Other studies have accounted for multicollinearity of maternal and paternal ages and found that advanced maternal age was the primary independent contributor of the parental age effect.…”
Section: Twomentioning
confidence: 99%
“…122,123 A 2012 meta-analysis found the relative risk (RR) of ASD for mothers aged 35 years or over compared to those aged 25 to 29 years to be 1.31 (95% CI: 1.19-1.45). 114 Since the most recent systematic review, 114 four studies have found significant associations between advanced maternal age and ASD 117,118,124,125 and one did not. 106 Some studies have found paternal and maternal ages to be independent risk factors for ASD after adjusting for spousal age, [126][127][128] and no evidence for a synergistic effect.…”
Section: Twomentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of autism spectrum disorders (ASD) is elevated when children are born to older parents (Sandin et al 2012;Bilder et al 2009;Parner et al 2012), as is incidence of Down syndrome (Sherman et al 2007), schizophrenia (Miller et al 2011), and behavioral problems (Gray, Indurkhya & McCormick 2004). Many other health conditions also are related to parental age.…”
mentioning
confidence: 99%
“…Developmental disorders are regarded as a congenital disease, whose cause is associated to some factors. Besides the maternal age, recent studies mention the effects of paternal age on risk of autism spectrum disorder, one of the developmental disorders [3][4][5]. Since tendency to marry later has advanced in developed countries, the mechanism of onset of developmental disorders is to be studied.…”
mentioning
confidence: 99%